Readiness of Libraries in Building Knowledgeable Society - Atiqa Nur Latifa Hanum (Record and Library Journal, 2022)
Background of the study: Facing the challenges of society 5.0, Pontianak as the city in West Kalimantan has maneuvered by establishing several libraries and parks with reading facilities in the potential areas. Three of them are in the tourist area on the Kapuas riverbank. Communities living around libraries have vulnerability due to environmental, economic, and educational problems. Purpose: To analyze the readiness of the three libraries in building a knowledgeable Kapuas riverbank communities. Method: Descriptive qualitative. Data collection techniques were carried out by observation, interviewing to 9 informants, and data documentation. Data analysis techniques consisted of data collection, reduction, presentation, and drawing conclusions. Findings: Long Fiah and Benua Melayu Laut Libraries have not yet ready to optimize their role as centers of education and information for communities due to the absence of library staff to manage the library, the difficulties in adding the collections, and the lack of promotion to communities. As a result, communities’ knowledge has not changed significantly. On the other hand, Bahagia Mendawai library has showed its role as a mediator and facilitator for communities to increase their knowledge. Even some innovations to foster a literacy culture can be seen from the Siberliterasi, JeLi, and Literacy Corner programs. Conclusion: As a first step in building a knowledgeable society, it is necessary to start from creating a literacy culture with strategic programs and commitment from library staff such as the literacy innovation program carried out by Bahagia Mendawai library. It is conducted by collaborating, adapting, and involving the community in library activities. The impact will help the community solving the problems. Pontianak will be better prepared to create a smart city with the support of knowledgeable communities.